Investigation of the removal of cations from aqueous solutions using sapropel - Albrektienė-Plačakė, Ramunė; Voišnienė, Violeta; Mucha Torre, Miguel (International Conference “Environmental Engineering”, 2026)
Sapropel is a sediment found at the bottom of lakes, consisting of both organic and inorganic materials. Water contains various cations, such as ammonium, calcium, and magnesium, which are generally harmless to human health; however, excessive concentrations of these ions can have negative effects. Although ammonium itself does not directly affect human health, it oxidizes into nitrites and nitrates when in contact with oxygen, and these compounds can be toxic. Similarly, while calcium and magnesium ions do not pose a health risk, they can damage pipes and shorten the lifespan of water-using electrical devices. Sapropel can be used as a biosorbent to remove these cations from aqueous solutions. It is inexpensive, eco-friendly, naturally occurring, easy to use, and sustainable. Various doses of sapropel, ranging from 1 to 50 g/L and mixing duration from 15 to 120 min., have been tested. Research has shown that using sapropel as a sorbent reduces the concentration of magnesium ions by 20%, calcium ions by 15.5%, ammonium – 57%. The optimal combination for ammonium ions was found 40 g/L of sapropel and ≥30 min of mixing.